The genome sequence of the Cow Parsley Leaf Beetle, Chrysolina oricalcia (O.F. Müller, 1776) [version 2; peer review: 2 approved, 1 approved with reservations] - Duncan Sivell; Olga Sivell; Michael Geiser (Wellcome Open Research, 2024)
We present a genome assembly from an individual Cow Parsley Leaf Beetle Chrysolina oricalcia (the Cow Parsley Leaf Beetle; Arthropoda; Insecta; Coleoptera; Chrysomelidae). The genome sequence is 1,423.4 megabases in span. Most of the assembly is scaffolded into 22 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 16.93 kilobases in length. Gene annotation of this assembly on Ensembl identified 35,990 protein coding genes.